Cerebriform intradermal nevus presenting as cutis verticis gyrata: A rare presentation - Prashansa Jaiswal; Akhilesh Shukla; Shiwangi Rana; Shilpi Shloka (Wolters Kluwer Medknow Publications, 2024)
Cerebriform intradermal nevus (CIN) is one of the causes for secondary cutis verticis gyrata (CVG). Here, we report a 9-year-old boy with well-demarcated swelling over the left temporal area of his scalp since birth. The swelling was about 15 cm × 10 cm in size with cerebriform folds. It was soft in consistency and loss of hair was present. Histopathology confirmed CIN. This report serves as an example of a rare case of secondary CVG due to a CIN.